Leveraging Actinide Hydrolysis Chemistry for Targeted Th and U Separations using Amidoxime‐Functionalized Poly(HIPE)s. Issue 11 (3rd May 2020) - Piechowicz, Marek; Chiarizia, Renato; Skanthakumar, S.; Rowan, Stuart J.; Soderholm, L.
Abstract: P olymerized h igh i nternal p hase e mulsions (poly(HIPE)s) are porous polymer monoliths whose synthesis can easily be tailored to allow incorporation of functional units. In this work, nitrile containing poly(HIPE)s have been prepared with either acrylonitrile (AN) or 4‐cyanostyrene (4CS) comonomers. Post‐synthetic modification of these nitrile‐containing poly(HIPE)s yields their corresponding amidoximated analogues, which were studied for actinide uptake. These amidoxime‐functionalized, porous polymers were shown to adsorb 95 % Th 4+ species from aqueous solution within 30 minutes. In contrast to other amidoxime containing polymers the uptake of UO2 2+ in these poly(HIPE)s is lower under similar conditions. A critical analysis of actinide separations and high‐energy X‐ray scattering data provides insight into the polymers' selectivity, enabled by the uptake of multinuclear Th clusters. Abstract : Amidoxime functionalized poly(high internal phase emulsions) are used for early actinide separations. The porous monoliths are found to have an unusual selectivity for Th versus U, achieving >90 % uptake in less than an hour. X‐ray scattering data suggests the presence of Th clusters within the polymer.